2006
DOI: 10.1038/sj.bjc.6603074
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin/paclitaxel/etoposide in extensive-stage small-cell lung cancer: a phase I–II study

Abstract: The aim of this study was to evaluate feasibility and toxicity of escalating doses of epirubicin and paclitaxel plus fixed dose of etoposide and to define the activity of the triplet in extensive disease small-cell lung cancer. Thirteen patients entered the phase I study: the maximum tolerated doses were epirubicin (EpiDX) 90 mg m À2 and paclitaxel (P) 175 mg m À2 with febrile neutropenia as dose-limiting toxicity. The recommended schedule for this regimen for the phase II study was EpiDX 75 mg m À2 , P 175 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The chromosomal location of both HER2 and TOP2A is 17q21-22 , . Epirubicin is a TOP2 inhibitor and is employed as a base in single or combination chemotherapy for solid tumors, including lung cancer cells . Several studies have indicated that HER2 and TOP2A overexpression is not significantly correlated with failure chemotherapy, patient survival, recurrence, or overall histologic grade , .…”
Section: Introductionmentioning
confidence: 99%
“…The chromosomal location of both HER2 and TOP2A is 17q21-22 , . Epirubicin is a TOP2 inhibitor and is employed as a base in single or combination chemotherapy for solid tumors, including lung cancer cells . Several studies have indicated that HER2 and TOP2A overexpression is not significantly correlated with failure chemotherapy, patient survival, recurrence, or overall histologic grade , .…”
Section: Introductionmentioning
confidence: 99%
“…20 The dosage was determined according to previous phase II studies in SCLC. 14 , 17 Patients with a history of BMs were included. Exclusion criteria were written or oral refusal to participate expressed during the lifetime, composite tumor or another subtype of lung carcinoma, and SCLC patients not treated with the study regimen.…”
Section: Methodsmentioning
confidence: 99%
“…15 Two phase II studies highlighted the activity of epirubicin in SCLC both as monotherapy or when combined with other drugs. 16 , 17 Recently, Pasello et al reported retrospective data of 68 patients treated with epirubicin at 70 mg/m 2 combined with paclitaxel at 135 mg/m 2 in the second line 18 and highlighted the efficacy of this association. Partial response (PR) and stable disease (SD) were obtained in 30% and 34% of cases, respectively, with a median PFS and OS reaching 21.8 and 26.5 weeks, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, combination chemotherapy is required and many medical oncologists are exploring new drug combinations for improved chemotherapy. A number of clinical trials have been carried out to verify the chemotherapy effect of combination use of ETP and paclitaxel (Dongiovanni, Buffoni, et al, ; Reck, von Pawel, et al, , ; Tibaldi, Prochilo, et al, ). A recent study indicated that the combination of PTX and ETP in a polymer–lipid hybrid nanoparticle system improved the efficacy for osteosarcoma in vitro (Duan, Li, et al, ).…”
Section: Introductionmentioning
confidence: 99%